HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN KEAKTIFAN BELAJAR ILMU PENGETAHUAN SOSIAL DI KELAS V SDN CILUAR 2 KECAMATAN BOGOR UTARA - Windiyani, Tustiyana (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2018)
This research belongs to correlation research. It consists of interpersonal communication as independent variable and learning activities as dependent variable. This study is aimed to know the correlation of interpersonal communication and learning activities of social sciences. This research was conducted in March 2018 and used survey research with correlational approach. The subject of this research is the students of grade V of Ciluar, in Bogor. The population of this research are 53 respondents. Data analysis techniques used are simple regression and correlation analysis techniques. The technique of simple regression and correlation analysis yields a model of correlation which is expressed in the form of regression equation that is Ŷ = 24,307 + 0,7164X, with price F count equal to 63,83 bigger than F tabel with real level 0,05 equal 4,03, and contribution based the results of research by 56%, it can be concluded that there is a positive and significant correlation between interpersonal communication and students' learning activities of Social Sciences. Learning includes transmitting information and communication therefore, from this research, a conclusion can be drawn that interpersonal communication should be possessed by each learner in the learning process. A teacher plays an important drawn in developing interpersonal communication skill and this can be achieved through the application of various learning models.Keywords: Interpersonal Communication, Learning Activities of social sciences.